Injectivity and chain conditions on y-closed submodules - Sahib, Lmyaa; AL-Bahraany, Bahar (Iraqi Journal of Science, 2023)
Let R be a commutative ring with identity and let M be a unital left Rmodule.Goodearl introduced the following concept :A submodule A of an R –module M is an y – closed submodule of M if is nonsingular.In this paper weintroduced an y – closed injective modules andchain condition on y – closedsubmodules.